Dancing with the impropriety of media: how Indonesian consumers think and behave towards the unethical and illogical online news - Wijaya, Bambang Sukma (Penerbit Universiti Kebangsaan Malaysia, 2019)
The rise of online media makes us now everyday are bombarded by a number of online news content which are sometimes unethical and illogical. Without considering the adverse effects it causes, the media continue to treat news consumers with inappropriate content. News consumers as if hypnotized to 'dance' following the rhythm of that impropriety. How do news consumers, especially in Indonesia, think and behave towards the issue? This paper captures the voices of consumers and reviews their judgements regarding the ethical and logical discourse of the news provided by online media. Research was conducted in two stages. The first stage was a qualitative approach through in-depth interviews with five active online news readers. The results identify three aspects related to unethical content: verbal, visual and news styles. Meanwhile, three other aspects concern issues of unethical news context, namely placement, links and news layout. The aspects related to illogical news refer to the issues of accuracy, coherency, and manipulation. The findings in the first stage serve as a basis for examining which aspects are the most concern for consumers in the second stage through a quantitative-descriptive approach involving 287 respondents. The results show that verbal and news styles, links and manipulation are the most dominant issues among consumers. Responding to the inappropriate news, consumers tend to perceive the media negatively, label it 'abal-abal' or fake and unprofessional, even blacklist it as prohibited media.